KINETIKA FAKTOR VON WILLEBRAND DEMAM BERDARAH DENGUE ORANG DEWASA - Riat El Khair; Usi Sukorini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
Dengue haemorrhagic fever (DHF) is still a problem in Indonesia. It is a syndrome that in most severe form may threaten the patient’slife, primarily through increased vascular permeability due to endothelial dysfunction leading to shock. Von Willebrand factor (vWf) is ablood glycoprotein involved in haemostasis and present in the blood plasma. The vWf is reported as one of dysfunction endothelial marker.However, there is limited information about the kinetics and contribution of vWf in the pathogenesis of DHF in adult patients. In thisstudy, a serial level of vWf was measured as kinetic of plasma vWf. It is expected that, the evidence based medicine will give contributionin the management of DHF patients. Also, in the future a study will be conducted especially about the prediction of shock to know thekinetic of plasma von Willebrand factor in adult dengue haemorrhagic fever patients. A cross-sectional repeated–measurement study wasconducted from October 2007 up to January 2008 in the Department of Clinical Pathology at the Sardjito General Hospital Yogyakarta.Subjects who met the eligible criteria were selected i.e. adult patients hospitalized in the Department of Internal Medicine diagnosed asDHF based on WHO criteria and antibody anti-dengue detection. Serial measurement of plasma vWf was determined on days five (5),seven (7) and 15 using enzyme linked fluorescent assay (ELFA) principle. The resulting data was shown graphically and the differencein levels of vWf among the three groups of time was analyzed by Friedman’s test. The study results showed an increase of vWf on dayfive /5 (218.48 %), followed by 187.08 % on day seven (7). Interestingly, there was a sharp increase of vWf on day 15 (233.80 %). Inaddition, there were statistically significant different levels of vWf among those three groups (p = 0.00) in adult dengue haemorrhagicfever patients with the von Willebrand kinetic factor showing a fluctuation pattern. There is an increased level of vWf on the fifth (5)day but a decrease on the seventh (7) day. However, there is a sharp increase in the convalescence phase.